Laminate, packaging bag, and package
A laminate with a polyethylene terephthalate film, nylon 6 film, and sealant layer, characterized by a high crystallinity index, addresses pinhole issues in packaging materials, ensuring robustness and hygiene by enhancing puncture strength.
Patent Information
- Application Number
- JP2023115330
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-13
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-06-19
AI Technical Summary
Conventional laminates used in packaging materials for pouches are prone to pinhole formation due to friction during transport, which can compromise the hygiene of the contents by allowing outside air or base layer components to enter.
A laminate structure comprising a polyethylene terephthalate film, a nylon 6 film, and a sealant layer, with a specific crystallinity index indicated by a ratio of peak intensities from X-ray diffraction, ensuring a high proportion of oriented crystals and low amorphous content, thereby enhancing puncture strength.
The laminate provides high puncture strength, reducing the likelihood of pinhole formation and maintaining the integrity of the packaging, thus preventing quality deterioration of stored items.
Smart Images

Figure 2025000523000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate, a packaging bag, and a packaging body. [Background technology]
[0002] Conventionally, a laminate including a base layer, an intermediate layer, and a sealant layer has been used as a packaging material for forming refill pouches, food pouches, etc. Patent Document 1 discloses a pouch packaging material that combines good appearance and puncture strength, including a biaxially oriented polyethylene terephthalate film as the base layer and a biaxially oriented nylon film as the intermediate layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-147369 A Summary of the Invention [Problem to be solved by the invention]
[0004] If a pinhole occurs in the laminate constituting the pouch due to friction during transportation of the pouch, etc., outside air or components of the base material layer may enter the pouch, which may affect the hygiene of the contents. Therefore, the present disclosure provides a laminate having a sufficiently high puncture strength, and a packaging bag and a packaging body including such a laminate. [Means for solving the problem]
[0005] One aspect of the present disclosure provides a laminate comprising a polyethylene terephthalate film, a nylon 6 film, and a sealant layer in this order, wherein when a surface of the laminate facing the polyethylene terephthalate film is measured by X-ray diffraction, the I1 / I0 ratio is 11.5 or greater, where I0 is the peak intensity value detected when 2θ is 19.5°, and I1 is the peak intensity value of the (002) plane of nylon 6.
[0006] The laminate has an I1 / I0 of 11.5 or more. The I1 / I0 is the ratio of peak intensities of oriented crystals and amorphous portions of nylon 6 obtained by X-ray diffraction, and can therefore be regarded as the crystallinity index of nylon 6. Therefore, when the surface of the laminate facing the polyethylene terephthalate film is measured by X-ray diffraction, the crystallinity index of the nylon 6 film is 11.5 or more, so that a laminate having a nylon 6 film with a low amorphous content and a high oriented crystal content can be obtained. Such a laminate has high puncture strength.
[0007] One aspect of the present disclosure provides a packaging bag including the laminate. The packaging bag includes the laminate, and thereby has high puncture strength.
[0008] According to one aspect of the present disclosure, there is provided a package including the above-described packaging bag and an item to be contained in a container of the packaging bag. The package includes the above-described laminate, and is therefore capable of preventing pinholes from being formed in the packaging bag. Thus, deterioration of the quality of the item can be sufficiently prevented. Effect of the Invention
[0009] The present disclosure can provide a laminate having a sufficiently high puncture strength in a laminate having a polyethylene terephthalate film, a nylon 6 film, and a sealant layer in this order, as well as a packaging bag and a packaging body including such a laminate. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 illustrates one embodiment of a cross-section of a laminate. [Diagram 2] FIG. 2 is an example of a plan view showing one embodiment of a package. [Diagram 3] FIG. 1 is an example of a plan view showing an embodiment of a packaging bag. [Figure 4] FIG. 2 is a diagram showing a peak pattern by X-ray diffraction measurement of nylon 6 film A in an example. [Diagram 5]FIG. 2 is a diagram showing a peak pattern by X-ray diffraction measurement of nylon 6 film C in the examples. [Figure 6] FIG. 2 is a diagram showing a peak pattern by X-ray diffraction measurement of polyethylene terephthalate film A in an example. [Figure 7] FIG. 2 is a diagram showing a peak pattern by X-ray diffraction measurement of polyethylene terephthalate film B in the examples. [Figure 8] 1 is a diagram in which the peak patterns of nylon 6 film A and polyethylene terephthalate film A are superimposed on the peak pattern obtained by X-ray diffraction measurement of the laminate in Example 1. [Figure 9] 1 is a diagram in which the peak patterns of a nylon 6 film C and a polyethylene terephthalate film B are superimposed on the peak pattern obtained by X-ray diffraction measurement of the laminate in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Hereinafter, an embodiment of the present disclosure will be described. However, the following embodiment is an example for explaining the present disclosure, and is not intended to limit the present disclosure to the following contents. The upper or lower limit of the numerical range specified in this disclosure may be replaced with any value shown in the examples. In addition, the upper and lower limits described individually may be arbitrarily combined. Unless otherwise specified, the materials or components exemplified in this disclosure may be used alone or in combination of two or more types. In the description, the same elements or elements having the same functions are given the same reference numerals, and duplicated descriptions are omitted. In addition, the positional relationships such as up, down, left, and right used in the description are based on the positional relationships shown in the drawings, unless otherwise specified.
[0012] 1 is a diagram showing one embodiment of a cross section of a laminate in the present disclosure. The laminate 100 has a nylon 6 film 20 and a sealant layer 30, in this order, on one side of a polyethylene terephthalate (PET) film 10. A first adhesive layer S1 is interposed between the PET film 10 and the nylon 6 film 20. A second adhesive layer S2 is interposed between the nylon 6 film 20 and the sealant layer 30. In addition, a printed layer 40 is interposed between the PET film 10 and the first adhesive layer S1.
[0013] The thickness of the PET film 10 is not particularly limited and may be 9 to 25 μm, 10 to 20 μm, or 10 to 15 μm. The thickness of the PET film 10 may be adjusted depending on the application or desired characteristics.
[0014] The PET content in the PET film 10 may be 50% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more of the total amount of the PET film 10.
[0015] The PET film 10 may be a commercially available one. The PET film 10 may be a stretched film or an unstretched film. It is believed that the orientation degree of the crystals in the polymer film is improved by stretching the film. Therefore, it is preferable to use a stretched film from the viewpoint of increasing the oriented crystals in the film and improving the puncture strength. The direction of stretching may be the MD direction or the TD direction. In addition, the stretching method may be any method that can provide a film with stable dimensions, such as uniaxial stretching, biaxial stretching, or a tubular method. From the viewpoint of further improving the puncture strength, a biaxially stretched film may be used as the PET film 10. The biaxially stretched film may be a biaxially stretched film obtained by a simultaneous biaxial stretching method or a sequential biaxial stretching method.
[0016] The thickness of the nylon 6 film 20 is not particularly limited and may be 10 to 25 μm, 10 to 20 μm, or 12 to 17 μm. The thickness of the nylon 6 film 20 may be adjusted depending on the application or desired characteristics.
[0017] The nylon 6 film 20 is a polymer film containing nylon 6, which is a synthetic polymer containing polyamide. The content of polyamide in the nylon 6 film 20 may be 50% by mass or more, 80% by mass or more, 90% by mass or more, or 95% by mass or more of the total amount of the nylon 6 film 20. Since the nylon 6 film 20 has excellent puncture strength and flexibility, the inclusion of the nylon 6 film 20 can further improve the puncture strength and flexibility of the laminate 100.
[0018] The nylon 6 film 20 may be a commercially available product. The nylon 6 film 20 may be a stretched film or an unstretched film. It is preferable to use a stretched film from the viewpoint of increasing the proportion of oriented crystals in the film and improving the puncture strength. The stretching direction may be the MD direction or the TD direction. The stretching method may be any method that can provide a film with stable dimensions, such as uniaxial stretching, biaxial stretching, or a tubular method. The biaxially stretched film obtained by biaxial stretching may be a simultaneous biaxial stretching method, or may be a sequential biaxial stretching method from the viewpoint of orienting the molecules inside the nylon 6 film 20 and improving the puncture strength. A nylon 6 film 20 obtained by a tubular method may be used from the viewpoint of sufficiently orienting the molecules inside the nylon 6 film 20 and further improving the puncture strength.
[0019] The sealant layer 30 is a layer that imparts heat-sealing properties to the laminate 100. The component of the sealant layer 30 may be, for example, a thermoplastic resin. Examples of the thermoplastic resin include polyolefin resins such as low-density polyethylene (LDPE), medium-density polyethylene (MDPE), linear low-density polyethylene (LLDPE), ethylene-vinyl acetate copolymer (EVA), and ethylene-α-olefin copolymer; ethylene resins such as ethylene-(meth)acrylic acid copolymer; blended resins of polyethylene and polybutene; homopolypropylene resin (PP); propylene-ethylene random copolymer, propylene-ethylene block copolymer, and polypropylene resins such as propylene-α-olefin copolymer. In addition, a mixture of a plurality of these thermoplastic resins may be used. These thermoplastic resins can be appropriately selected depending on the intended use.
[0020] The resin constituting the sealant layer 30 may contain various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, and a tackifier.
[0021] The sealant layer may be a stretched film (for example, a stretched polypropylene film), or from the viewpoint of improving the sealability by heat sealing, may be a non-stretched film (for example, a non-stretched polypropylene film).
[0022] The thickness of the sealant layer 30 can be adjusted depending on the mass of the contents or the shape of the packaging bag, and may be about 10 to 100 μm.
[0023] A first adhesive layer S1 is interposed between the PET film 10 and the nylon 6 film 20. A second adhesive layer S2 is interposed between the nylon 6 film 20 and the sealant layer 30. Examples of materials for the adhesive layer include polyester-isocyanate resins, urethane resins, and polyether resins. The first adhesive layer S1 can bond the PET film 10 and the nylon 6 film 20 more firmly. The second adhesive layer S2 can bond the nylon 6 film 20 and the sealant layer 30 more firmly. The material of the first adhesive layer S1 and the material of the second adhesive layer S2 may be the same or different from each other.
[0024] The thickness of the first adhesive layer S1 and the second adhesive layer S2 is not particularly limited, and may be, for example, 0.5 to 5 μm, or 2 to 3 μm. When the thickness of the first adhesive layer S1 is 0.5 μm or more, the adhesion between the PET film 10 and the nylon 6 film 20 can be improved. When the thickness of the second adhesive layer S2 is 0.5 μm or more, the adhesion between the nylon 6 film 20 and the sealant layer 30 can be improved. When the thickness of the first adhesive layer S1 and the second adhesive layer S2 is 5 μm or less, the recyclability of the laminate 100 can be improved. The thickness of the first adhesive layer S1 and the thickness of the second adhesive layer S2 may be the same as or different from each other.
[0025] The first adhesive layer S1 and the second adhesive layer S2 are layers that bond two adjacent layers together when forming the laminate 100. The laminate 100 can be formed by laminating the nylon 6 film 20 on the PET film 10, and then laminating the sealant layer 30 to the nylon 6 film 20. The laminate 100 can be formed by a dry lamination method in which the layers are laminated with an adhesive such as a one-component curing or two-component curing urethane adhesive, a non-solder dry lamination method, and an extrusion lamination method in which the above-mentioned thermoplastic resin is heated and melted, extruded in a curtain shape, and laminated. The adhesive used when laminating the nylon 6 film 20 to the PET film 10 forms a first adhesive layer S1 as shown in FIG. 1. The adhesive used when laminating the sealant layer 30 to the nylon 6 film 20 forms a second adhesive layer S2 as shown in FIG. 1.
[0026] A printing layer 40 can be provided on the surface of the PET film 10 facing the nylon 6 film 20. The printing layer 40 is provided at a position visible from the outside of the laminate for the purpose of displaying information about the contents, identifying the contents, or improving the design of the packaging bag. The printing method and printing ink are not particularly limited, and are appropriately selected from known printing methods and printing inks in consideration of printability on the film, design such as color tone, adhesion, safety as a food container, and the like. Examples of printing methods that can be used include gravure printing, offset printing, gravure offset printing, flexographic printing, and inkjet printing. From the viewpoints of productivity and high definition of the image, gravure printing may be used.
[0027] In order to improve the adhesion of the printed layer 40, the surface of the PET film 10 on the side of the printed layer 40 may be subjected to various pretreatments such as corona treatment, plasma treatment, and frame treatment, or a coating layer such as an easy-adhesion layer may be provided.
[0028] By performing X-ray diffraction measurement on the surface X (surface of the PET film 10) on the PET film 10 side of the laminate 100, a peak pattern showing the crystalline state of the nylon 6 film 20 and the PET film 10 can be obtained. Among the peaks obtained by X-ray diffraction measurement, the peak intensity value of the halo peak (diffraction line derived from amorphous material) detected at 2θ of 19.5° is I0, the peak intensity value of the (002) plane of nylon 6 is I1, and the peak intensity value of the (100) plane of PET is I2. When the crystallinity index is high, the proportion of oriented crystals in the film increases, and the puncture strength tends to be high. X-ray diffraction measurement can be performed, for example, using an X-ray diffractometer (RINT ULTIMA III, manufactured by Rigaku Corporation), with an X-ray source of Cu-Ka rays, a diffraction angle of 10°<2θ<40°, a voltage of 40 kV, and a current of 40 mA. The peak intensity value represents the height of the peak relative to the baseline (cps).
[0029] Pre-processing such as smoothing of the peak pattern obtained by X-ray diffraction measurement and background processing may be performed by a known method that is installed as standard in the X-ray diffraction device. Examples of methods for background processing of the peak pattern include the manual (spline) method and the SONNVELT-VISSEER method. In the present disclosure, the manual (spline) method is used from the viewpoint of reducing the variation in peak intensity after background processing and improving accuracy. The manual (spline) method is a method in which two 2θ positions are specified, and a spline approximation line passing through the two points is used as the background. The minimum value of the 2θ position may be 5 to 15°. The maximum value of the 2θ position may be 35 to 45°.
[0030] By X-ray diffraction measurement, a broad halo peak derived from amorphous matter is usually detected at 2θ of about 19.5°. Such a halo peak is derived from amorphous matter contained in the nylon 6 film 20, the PET film 10, or the sealant layer 30 in the laminate 100. By specifying the 2θ at which the halo peak is detected as 19.5°, the influence of overlap with other peaks can be sufficiently reduced, and the variation in the peak intensity value (I0) of the halo peak can be suppressed. Examples of the other peaks include those derived from the (130) plane (2θ≒18.5°) of polypropylene when a non-oriented polypropylene (CPP) film used as the sealant layer 30 is used, the (111) plane (2θ≒21.4°) of polypropylene when a CPP film is used, and the (200) plane (2θ≒20°) of the nylon 6 film.
[0031] Among the peaks obtained by X-ray diffraction, the halo peak (2θ=19.5°) with a peak intensity value of I0 is manually specified using the analysis software attached to the X-ray diffraction apparatus, but the peak on the (002) plane of nylon 6 with a peak intensity value of I1 and the peak on the (100) plane of PET with a peak intensity value of I2 are automatically detected by peak search processing using the analysis software attached to the X-ray diffraction apparatus.
[0032] X-ray diffraction measurements show a peak at 2θ of around 24° that is attributable to the (002) plane of nylon 6. The presence of such a peak attributable to the (002) plane of nylon 6 confirms that a high proportion of crystals oriented in a specific direction are present in the nylon 6 film. The reason for selecting the (002) plane is that the peak attributable to this crystal plane is usually the largest in stretched nylon 6 films.
[0033] X-ray diffraction measurements show a peak at 2θ of around 26° that is attributable to the (100) plane of PET. The presence of such a peak attributable to the (100) plane of PET confirms that a high proportion of crystals oriented in a specific direction are present in the PET film. The reason for selecting the (100) plane is that the peak attributable to this crystal plane is usually the largest in stretched PET films.
[0034] When X-ray diffraction measurement is performed on the laminate 100, the I1 / I0 is 11.5 or more. Such a laminate 100 has a high puncture strength due to a low amorphous content in the laminate and a high oriented crystal content of the nylon 6 film.
[0035] I1 / I0 may be 12.0 or more, 13.0 or more, or 14.0 or more. When I1 / I0 is in such a range, a laminate including a nylon 6 film having a lower amorphous content and a higher oriented crystal content can be obtained. Therefore, such a laminate has a higher puncture strength. I1 / I0 may be 20.0 or less.
[0036] The average value of I1 / I0 may be 12.0 or more, 12.5 or more, or 13.0 or more. The average value of I1 / I0 may be 20.0 or less. The average value may be calculated by measuring a plurality of positions of one laminate 100, or may be calculated by measuring a plurality of laminate samples obtained by dividing the laminate 100. The number n for measuring the average value may be 5 or more, 7 or more, or 10 or more. From the viewpoint of suppressing variation, the number n may be 20 or less.
[0037] The I2 / I0 may be 10.6 or more when X-ray diffraction measurement is performed on the laminate 100. Such a laminate 100 has a high puncture strength due to the low ratio of amorphous matter in the laminate.
[0038] I2 / I0 may be 11.0 or more, or 12.0 or more. When I2 / I0 is in such a range, a laminate having a lower amorphous content can be obtained. Therefore, such a laminate has a higher puncture strength. I2 / I0 may be 20.0 or less.
[0039] The average value of I2 / I0 may be 11.0 or more, 11.5 or more, or 12.0 or more. The average value of I2 / I0 may be 20.0 or less. The average value may be calculated by measuring a plurality of positions on one laminate 100, or may be calculated by measuring a plurality of laminate samples obtained by dividing the laminate 100. The number n for measuring the average value may be 5 or more, 7 or more, or 10 or more. From the viewpoint of suppressing variation, the number n may be 20 or less.
[0040] The puncture strength of the laminate 100 can be measured based on "7.5 Puncture Strength Test" of JIS Z1707:2019 "General Rules for Food Packaging Plastic Films". For example, the measurement can be performed by using a Tensilon AD-7303 (manufactured by A&D Co., Ltd.) to pierce the laminate 100 from the surface X on the PET film 10 side toward the opposite side. The puncture strength of the laminate 100 may be 17N or more, 18N or more, or 19N or more. By providing the laminate 100 having such a puncture strength, a packaging bag having a high puncture strength can be obtained. The puncture strength of the laminate 100 may be 25N or less.
[0041] The average value of the puncture strength of the laminate 100 may be 16N or more, 17N or more, or 18N or more. By providing the laminate 100 having such a puncture strength, a packaging bag having high puncture strength can be obtained. The average value may be calculated by measuring a plurality of positions of the laminate 100, or may be calculated by measuring a plurality of laminate samples obtained by dividing the laminate 100 into a plurality of pieces. The number n for measuring the average value may be 5 or more, 7 or more, or 10 or more. From the viewpoint of suppressing variation, the number n may be 20 or less. The average value of the puncture strength of the nylon 6 film 20 may be 30N or less.
[0042] The laminate 100 may include a nylon 6 film 20 having an I1 / I0 of 25 or more when the surface of the nylon 6 film alone is measured by X-ray diffraction. When the nylon 6 film alone is subjected to X-ray diffraction measurement, the I1 / I0 may be 26 or more, or may be 27 or more. The laminate 100 including such a nylon 6 film 20 has high puncture strength because the proportion of amorphous matter in the nylon 6 film is low and the proportion of oriented crystals is high. When the nylon 6 film alone is subjected to X-ray diffraction measurement, the I1 / I0 may be 35 or less.
[0043] The laminate 100 may include a nylon 6 film 20 having an average I1 / I0 value of 25 or more when the surface of the nylon 6 film alone is measured by X-ray diffraction. The average I1 / I0 value when the nylon 6 film alone is subjected to X-ray diffraction measurement may be 26 or more, or may be 28 or more. The laminate 100 including such a nylon 6 film 20 has high puncture strength because the proportion of amorphous matter in the nylon 6 film is low and the proportion of oriented crystals is high. The average I1 / I0 value when the nylon 6 film alone is subjected to X-ray diffraction measurement may be 35 or less. The average value may be calculated by measuring multiple locations on the nylon 6 film 20, or may be calculated by measuring multiple nylon 6 film samples obtained by dividing the nylon 6 film 20 into multiple pieces. The number n for measuring the average value may be 5 or more, 7 or more, or 10 or more. From the viewpoint of suppressing variation, the number n may be 20 or less.
[0044] The laminate 100 may include a PET film 10 having an I2 / I0 of 41 or more when the surface of the PET film alone is measured by X-ray diffraction. When the PET film alone is subjected to X-ray diffraction measurement, the I2 / I0 may be 42 or more, or may be 43 or more. The laminate 100 including such a PET film 10 can improve the cuttability, heat resistance, and visibility of the printed layer. When the PET film alone is subjected to X-ray diffraction measurement, the I2 / I0 may be 65 or less.
[0045] The laminate 100 may include a PET film 10 having an average I2 / I0 value of 48 or more when the PET film is subjected to X-ray diffraction measurement. The average I2 / I0 value of the PET film alone may be 50 or more. The laminate 100 including such a PET film 10 can improve the cuttability, heat resistance, and visibility of the printed layer. The average I2 / I0 value of the PET film alone when X-ray diffraction measurement is performed may be 65 or less. This average value may be calculated by measuring a plurality of positions of the PET film 10, or may be calculated by dividing the PET film 10 into a plurality of parts and measuring each of them. The number n for measuring the average value may be 5 or more, 7 or more, or 10 or more. From the viewpoint of suppressing the variation, the number n may be 20 or less.
[0046] The reason why the I1 / I0 and I2 / I0 values obtained when measuring the film alone are larger than the I1 / I0 and I2 / I0 values obtained when measuring the laminate is that when measuring the laminate, the value of the halo peak (I0) detected at 2θ=19.5° is somewhat larger due to the influence of other layers such as the sealant layer and PET film, and it is thought that the crystallinity of each film is somewhat reduced by laminating each film into a laminate.
[0047] The puncture strength of the nylon 6 film 20 may be 11.5 N or more, or may be 12.0 N or more. By providing the nylon 6 film 20 having such a puncture strength, it is possible to further improve the puncture strength of the laminate 100. The puncture strength of the nylon 6 film 20 may be 20.0 N or less.
[0048] The average value of the puncture strength of the nylon 6 film 20 may be 11.0 N or more, 12.0 N or more, or 13.0 N or more. By providing the nylon 6 film 20 having such a puncture strength, the puncture strength of the laminate 100 can be further improved. The average value may be calculated by measuring a plurality of positions of the nylon 6 film 20, or may be calculated by dividing the nylon 6 film 20 into a plurality of parts and measuring each of them. The number n for measuring the average value may be 5 or more, 7 or more, or 10 or more. From the viewpoint of suppressing variation, the number n may be 20 or less. The average value of the puncture strength of the nylon 6 film 20 may be 20.0 N or less.
[0049] The puncture strength of the PET film 10 may be 6.0 N or more, or may be 7.0 N or more. By providing a PET film 10 having such a puncture strength, it is possible to further improve the puncture strength of the laminate 100. In addition, the puncture strength of the PET film 10 may be 10.0 N or less.
[0050] FIG. 2 is an example of a plan view showing one embodiment of a package formed using the laminate 100. The package 200 includes a packaging bag 300 and an object 21 accommodated in the accommodation section 22 of the packaging bag 300. The packaging bag 300 is composed of two laminates 100a and 100b forming the side surfaces and a laminate 100c (gusset sheet) forming the bottom surface. The packaging bag 300 has an upper end seal section 31 (seal section 32) at the upper end, side end seal sections 33 and 34 (seal section 32) at both side ends, and lower end seal sections 35 and 36 (seal section 32) at the lower end. The upper end seal section 31 and the side end seal sections 33 and 34 are formed by overlapping and heat sealing the sealant layers 30 at the ends of the laminates 100a and 100b.
[0051] The bottom end seal portion 35 (gusset seal portion) is formed by overlapping and heat-sealing the sealant layers 30 at the ends of the laminates 100a and 100c. The bottom end seal portion 36 (gusset seal portion) is formed by overlapping and heat-sealing the sealant layers 30 at the ends of the laminates 100b and 100c. The structures of the laminates 100a, 100b, and 100c may be the same as the structure of the laminate 100 shown in FIG. 1.
[0052] The sealant layers 30 of the laminates 100a, 100b, and 100c are heat-sealed to each other at the upper end seal portion 31, the side end seal portions 33 and 34, and the lower end seal portions 35 and 36. That is, the dotted portions in FIG. 2 indicate the seal portions formed by heat sealing. The laminates 100a, 100b, and 100c are not heat-sealed (non-sealed portions) in the portions other than these seal portions. The laminates 100a, 100b, and 100c constituting the packaging bag 300 form an internal space (accommodating portion 22) for accommodating the contents 21 by sealing each seal portion. In this manner, the accommodating portion 22 is surrounded by the laminates 100a, 100b, and 100c.
[0053] The package 200 may be manufactured using a packaging bag 301 shown in Fig. 3. In the packaging bag 301, the upper end 31a of the laminate 100a (100b) is not heat-sealed. Before the upper end 31a is heat-sealed, the contents 21 are placed through an opening formed by the upper end 31a, and then the upper end 31a of the laminate 100a (100b) is heat-sealed. By forming the upper end seal portion 31 in this manner, the packaging bag 300 and the package 200 shown in Fig. 2 in which the contents 21 are sealed in the storage portion 22 of the packaging bag 300 can be obtained.
[0054] A pair of notches 41, 41 are provided in the side end seal portions 33, 34 of the packaging bag 300. A planned cutting line (not shown) may be provided connecting the pair of notches 41, 41. After heating the packaging body 200 in a microwave oven, the end user can open the packaging body 200 from one of the notches 41 along the planned cutting line and take out the heated contents 21.
[0055] The contents 21 are not particularly limited, and may contain not only water but also oils and fats. When oils and fats are contained, the temperature may become high locally. Even if the package 200 becomes high temperature when heated in a microwave oven, the steam vent can be formed with high precision as expected. Therefore, the occurrence of leakage due to delamination between the laminates 100a, 100b, 100c and bag breakage can be sufficiently suppressed. Examples of the contents 21 include foods such as curry, stew, soup, boiled food, and grilled food. However, the contents 21 are not limited to these.
[0056] The side end seal portion 34 includes a steam release portion 50 configured to be able to form a steam vent that communicates the storage portion 22 with the outside of the packaging bag 300 when the pressure in the storage portion 22 of the packaging bag 300 increases. The steam release portion 50 protrudes toward the center C of the packaging bag 300. When the contents 21 in the storage portion 22 are heated by a microwave oven to generate steam, the storage portion 22 expands. The forces applied to the upper end seal portion 31, the side end seal portions 33, 34, and the lower end seal portions 35, 36 due to the expansion become larger as the distance from the center C becomes shorter. Therefore, the steam release portion 50 protruding toward the center C is subjected to a large tensile stress as the contents 21 are heated. At this time, the laminate 100 has a high puncture strength, so that the occurrence of pinholes can be sufficiently suppressed.
[0057] When the pressure in the storage section 22 reaches or exceeds a predetermined value, the side edge seal portion 34 peels away from the inner edge in the steam release section 50, and the storage section 22 communicates with the outside of the packaging bag 300 (packaging body 200). In this way, steam is released to the outside through the steam vent hole (steam vent hole) formed in the steam release section 50. In this way, the steam release section 50 has the function of forming a steam vent hole when the pressure in the storage section 22 rises, thereby preventing the packaging bag 300 (packaging body 200) from breaking.
[0058] In the steam release section 50, a non-sealed section 53 is provided on the outside of the side end sealed section 34. As a result, the seal width of the side end sealed section 34 in the steam release section 50 is smaller than the seal width of the side end sealed section 34 other than the steam release section 50. For this reason, when the pressure inside the accommodating section 22 increases, a steam passage port (steam release port) that communicates the accommodating section 22 with the outside is smoothly formed in the steam release section 50. To sufficiently facilitate steam release (exhaust) from the accommodating section 22 to the outside, the non-sealed section 53 may be provided with a through hole that penetrates in the stacking direction of the stacks 100a, 100b.
[0059] The minimum seal width of the side end seal portion 34 in the steam release portion 50 may be 1 to 5 mm, or may be 2 to 4 mm. This allows steam to be released smoothly during heating in a microwave oven while maintaining good sealing properties. The shape and position of the steam release portion 50 are not particularly limited. In a modified example, the steam release portion 50 may be provided in the upper end seal portion 31 or the side end seal portion 33. Regardless of the shape and position, the minimum seal width of the steam release portion 50 may be in the above-mentioned numerical range. A plurality of steam release portions 50 may be provided.
[0060] The packaging bag 300 (package 200) may be subjected to a retort treatment in which the packaging bag 300 (package 200) is heated in a hot water spray exceeding 100° C. for 10 minutes or more.
[0061] Although several embodiments of the present disclosure have been described above, the present disclosure is not limited to the above-mentioned embodiments. A predetermined intermediate layer may be provided between each layer of the laminate 100 in order to improve the function of the laminate 100. The configuration of the intermediate layer may be appropriately referred to the contents described in the configuration of the sealant layer 30 above. By providing the laminate 100 with an intermediate layer, deformation of the laminate during the manufacture of the packaging bag can be further reduced. A plurality of intermediate layers may be used depending on the application of the laminate 100.
[0062] The laminate 100 may include, for example, a metal layer. Examples of the metal layer include copper foil, aluminum foil, tin foil, and indium foil. From the viewpoint of preventing the transmission of visible light and ultraviolet light, the metal layer may include aluminum foil. The thickness of the metal layer may be, for example, 6 to 9 μm. By making the thickness of the metal layer 6 μm or more, the piercing strength of the laminate 100 is improved. Therefore, even if a foreign matter adheres to the PET film 10 in a packaging bag including the laminate 100, the problem of the foreign matter penetrating the inner side of the PET film 10 can be prevented. Therefore, deterioration of the quality of the contents can be suppressed. The metal layer may be a deposition layer that is previously deposited on any of the layers constituting the laminate. Examples of deposition materials used for the deposition layer include metals such as Si, Al, Sn, In, Zn, Fe, and Mn, and inorganic compounds containing one or more of these metals. Examples of the inorganic compound include silicon oxides (SiOx) such as silicon monoxide and silicon dioxide, aluminum oxide, magnesium oxide, tin oxide, indium oxide, etc. In addition to these inorganic compounds, the inorganic compound may contain at least one metal selected from the group consisting of Si, Al, Sn, In, Zn, Fe, and Mn, or an oxide thereof.
[0063] The laminate 100 may include, for example, an anchor coat layer adjacent to at least one selected from the printed layer 40 and the metal layer. By including the anchor coat layer, the adhesion of the printed layer 40 or the metal layer can be increased, and the puncture strength of the laminate 100 can be further improved. The anchor coat layer can be formed by applying an anchor coat agent onto a predetermined layer and drying it. Examples of the anchor coat agent include polyester-based polyurethane resin and polyether-based polyurethane resin. The thickness of the anchor coat layer is not particularly limited and may be 0.1 to 1 μm, or 0.3 to 0.5 μm.
[0064] The PET film 10 and the nylon 6 film 20 may be directly bonded to each other without the first adhesive layer S1. Also, the nylon 6 film 20 and the sealant layer 30 may be directly bonded to each other without the second adhesive layer S2.
[0065] The present disclosure includes the following embodiments. [1] A laminate comprising a polyethylene terephthalate film, a nylon 6 film, and a sealant layer in this order, A laminate, wherein the surface of the laminate on the side of the polyethylene terephthalate film is measured by X-ray diffraction, and when the peak intensity value detected when 2θ is 19.5° is I0 and the peak intensity value of the (002) plane of nylon 6 is I1, I1 / I0 is 11.5 or more. [2] The laminate according to [1], wherein, when the surface is measured by X-ray diffraction, the peak intensity value of the (100) plane of polyethylene terephthalate is defined as I2, and I2 / I0 is 10.6 or more. [3] The laminate according to the above [1] or [2], wherein the nylon 6 film is a stretched film obtained by a tubular process. [4] The laminate according to any one of the above [1] to [3], which has a puncture strength of 17 N or more. [5] The laminate according to any one of the above [1] to [4], comprising the nylon 6 film, wherein, when a surface of the nylon 6 film alone is measured by X-ray diffraction, the I1 / I0 ratio is 25 or more, where I0 is the peak intensity value detected when 2θ is 19.5°, and I1 is the peak intensity value of the (002) plane of nylon 6. [6] The laminate according to any one of the above [1] to [5], comprising the polyethylene terephthalate film, in which, when a surface of the polyethylene terephthalate film alone is measured by X-ray diffraction, the I2 / I0 ratio is 41 or more, where I0 is the peak intensity value detected when 2θ is 19.5°, and I2 is the peak intensity value of the (100) plane of the polyethylene terephthalate. [7] The laminate according to any one of the above [1] to [6], wherein the nylon 6 film has a puncture strength of 11.5 N or more. [8] The laminate according to any one of the above [1] to [7], wherein the nylon 6 film has a thickness of 10 to 25 μm. [9] The laminate according to any one of the above [1] to [8], wherein the polyethylene terephthalate film has a thickness of 9 to 25 μm.
[10] A packaging bag comprising the laminate according to any one of the above [1] to [9].
[11] A package comprising the packaging bag described in
[10] above and an item contained in the storage section of the packaging bag. EXAMPLES
[0066] The present disclosure will be described in more detail below with reference to examples and comparative examples. Note that the present disclosure is not limited to the following examples.
[0067] [Film preparation] A commercially available nylon 6 film and a commercially available polyethylene terephthalate (PET) film were prepared. In addition, a commercially available non-oriented polypropylene (CPP) film with a thickness of 60 μm was prepared as a sealant layer.
[0068] Nylon 6 film A, nylon 6 film B, and nylon 6 film C were prepared from different manufacturers. Nylon 6 film A was a stretched film obtained by the tubular method, nylon 6 film B was a biaxially stretched film obtained by the sequential biaxial stretching method, and nylon 6 film C was a biaxially stretched film obtained by the simultaneous biaxial stretching method. All nylon 6 films had a thickness of 15 μm.
[0069] As PET films, PET film A and PET film B were prepared from different manufacturers. Both PET film A and PET film B were biaxially stretched films obtained by simultaneous biaxial stretching. Both PET films had a thickness of 12 μm.
[0070] [X-ray diffraction measurements of nylon 6 film, PET film, and CPP film] Each nylon 6 film, each PET film, and CPP film was cut to obtain a sample piece of 4.8 cm x 4.8 cm. The obtained sample piece was measured under the following conditions using RINT ULTIMA III (manufactured by Rigaku Corporation). For the peak pattern of each film obtained, leveling processing was performed at 19 points, and two points, 2θ = 10 ° and 2θ = 40 °, were selected, and background processing was performed between the two points by the manual (spline) method. The peak pattern of nylon 6 film A after background processing is shown in Figure 4, the peak pattern of nylon 6 film C in Figure 5, the peak pattern of PET film A in Figure 6, and the peak pattern of PET film B in Figure 7. Since it was confirmed that there was no diffraction line originating from the sample due to Cu-Kβ rays, a Ni filter was not used to prevent a decrease in the intensity of the diffraction line originating from the sample due to Cu-Kα rays.
[0071] X-ray source: Cu-Ka Voltage: 40kV ·Current: 40mA Scan method: 2θ-θ method (parallel beam method) Counting unit: cps Scanning speed: 4° / min Measurement range: 10°<2θ<40° Sampling speed: 0.020° / min -Sample stage control mode: Rotation Ni filter: Not used
[0072] Each nylon 6 film, each PET film, and each CPP film was cut as described above to prepare five sample pieces of 4.8 cm x 4.8 cm, and the above-mentioned X-ray diffraction measurement was carried out for each sample piece.
[0073] From the peak pattern of the nylon 6 film after background processing, the peak intensity value at 2θ of 19.5° was defined as I0, and the peak intensity value originating from the (002) plane of nylon 6 occurring at 2θ of around 23.7° was defined as I1. The crystallinity index of each sample piece of nylon 6 film, expressed as I1 / I0, was calculated. The average crystallinity index value was also calculated for each film. The results are shown in Table 1.
[0074] From the peak pattern of the PET film after background processing, the peak intensity value when 2θ is 19.5° was defined as I0, and the peak intensity value originating from the (100) plane of PET occurring at 2θ around 26° was defined as I2. The crystallinity index of each sample piece of PET film, expressed as I2 / I0, was calculated. The average crystallinity index value was also calculated for each film. The results are shown in Table 1.
[0075] [Measurement of puncture strength of nylon 6 film and PET film] The puncture strength of each sample piece subjected to the above X-ray measurement was measured under the following conditions based on "7.5 Puncture Strength Test" of JIS Z1707:2019 "General Rules for Food Packaging Plastic Films". The measuring device used was Tensilon AD-7703 (manufactured by A&D Co., Ltd.). The average puncture strength was calculated for each film. The results are shown in Table 1.
[0076] Test speed: 50mm / min Load cell: 100N Load range: 20N (20%)
[0077] [Table 1]
[0078] As shown in Table 1, a comparison of the crystallinity index and puncture strength of the films alone was made, and a positive correlation was found between the crystallinity index and puncture strength for nylon 6 films. The nylon 6 films produced by the sequential biaxial stretching method showed higher puncture strength than the nylon 6 films produced by the simultaneous biaxial stretching method. It was also confirmed that the nylon 6 films produced using the tubular method had even higher crystallinity index and puncture strength than the nylon 6 films produced by the sequential biaxial stretching method. On the other hand, for PET films, although PET film A showed a higher crystallinity index than PET film B, there was no change in puncture strength, and no correlation was found between the crystallinity index and puncture strength.
[0079] [Laminated body production] Example 1 A laminate was prepared according to the following procedure. A printed layer was formed on one side of the PET film A prepared in [Preparation of film]. The thickness of the printed layer was 1 μm. Next, nylon 6 film A and a CPP film were laminated in this order on top of the printed layer by dry lamination. The prepared laminate was cut into sample pieces measuring 4.8 cm x 4.8 cm. The layer structure of the laminate is shown below. PET film A / printing layer / first adhesive layer / nylon 6 film A / second adhesive layer / CPP film
[0080] Example 2 A laminate was produced in the same manner as in Example 1, except that Nylon 6 film B was used instead of Nylon 6 film A. The produced laminate was cut into sample pieces of 4.8 cm x 4.8 cm. The layer structure of the laminate is shown below. PET film A / printing layer / first adhesive layer / nylon 6 film B / second adhesive layer / CPP film
[0081] Comparative Example 1 A laminate was produced in the same manner as in Example 1, except that the PET film A used in Example 1 was replaced with the PET film B, and the nylon 6 film A was replaced with the nylon 6 film C. The produced laminate was cut into sample pieces of 4.8 cm x 4.8 cm. The layer structure of the laminate is shown below. PET film B / printed layer / first adhesive layer / nylon 6 film C / second adhesive layer / CPP film
[0082] [X-ray diffraction and puncture strength measurements for each laminate] Nine sample pieces of each laminate produced were prepared, and X-ray diffraction measurements were performed on the surface on the PET film side to calculate the crystallization indices I1 / I0 and I2 / I0 for the laminate. The conditions for the X-ray diffraction measurements were as described above. Then, the puncture strength measurements were performed in the direction from the surface of the PET film of the laminate to the opposite side. The conditions for measuring the puncture strength were as described above. The results are shown in Table 2. In Table 2, I1 / I0 is referred to as the "crystallization index α" and I2 / I0 is referred to as the "crystallization index β" among the crystallization indices.
[0083] Fig. 8 shows the peak pattern of the laminate of Example 1, the peak pattern of Nylon 6 film A in Fig. 4, and the peak pattern of PET film A in Fig. 6, all superimposed on each other. Fig. 9 shows the peak pattern of the laminate of Comparative Example 1, the peak pattern of Nylon 6 film C in Fig. 5, and the peak pattern of PET film B in Fig. 7, all superimposed on each other.
[0084] As shown in Fig. 8, when the peak patterns of the X-ray diffraction measurement of the nylon 6 film A, the PET film A, and the laminate of Example 1 were superimposed, the peaks of the (002) plane of the nylon 6 film A and the (100) plane of the PET film A overlapped with the peaks of the laminate of Example 1. In addition, as shown in Fig. 9, when the peak patterns of the X-ray diffraction measurement of the nylon 6 film C, the PET film B, and the laminate of Comparative Example 1 were superimposed, the peaks of the (002) plane of the nylon 6 film C and the (100) plane of the PET film B overlapped with the peaks of the laminate of Comparative Example 1. Therefore, it was confirmed that the peak pattern by the X-ray diffraction measurement of the laminate was derived from the crystalline state of the film used.
[0085] [Preparation of packaging bags and evaluation after retort treatment] Example 3 A laminate having the layer structure of Example 1 was prepared so as to have a size of 100 mm long x 200 mm wide. The prepared laminate was folded, and the sides and bottom were heat-sealed together so that the seal width was 5 to 10 mm, to prepare a packaging bag as shown in FIG. 3. Specifically, the side end seal parts and the bottom end seal part other than the steam release part were heat-sealed by the impulse method (temperature: 190°C), and then the steam release part was formed by heat sealing using a mold. Thereafter, 100 g of water was placed in the storage part, and the upper end part was heat-sealed by the impulse method (temperature: 190°C) to form the upper end seal part. In this way, a standing pouch (packaging bag and package) in which water was sealed in the storage part was obtained as shown in FIG. 2.
[0086] The package produced by spray treatment at 120°C for 30 minutes was subjected to retort treatment, and the sealed portion was peeled off to produce a laminate after retort treatment. The laminate after retort treatment was then cut into sample pieces of 4.8 cm x 4.8 cm. In this manner, nine sample pieces of the laminate after retort treatment were prepared. The above-mentioned X-ray diffraction measurement and puncture strength measurement were performed to evaluate the crystallinity index α, crystallinity index β, and puncture strength of the laminate after retort treatment. The respective results are shown in Table 3.
[0087] Example 4 A retort-treated laminate was produced in the same manner as in Example 3, except that the laminate of Example 1 was replaced with the laminate of Example 2 to produce the above-mentioned pouch. X-ray diffraction measurement and puncture strength measurement were performed in the same manner as described above to evaluate the crystallinity index α, crystallinity index β, and puncture strength of the retort-treated laminate. The results are shown in Table 3.
[0088] Comparative Example 2 A laminate after retort treatment was produced in the same manner as in Example 3, except that the laminate of Example 1 was replaced with the laminate of Comparative Example 1 to produce the above-mentioned pouch. The number of sample pieces was five. The above-mentioned X-ray diffraction measurement and puncture strength measurement were performed to evaluate the crystallinity index α, crystallinity index β, and puncture strength of the laminate after retort treatment. The results are shown in Table 3.
[0089] [Table 2]
[0090] [Table 3]
[0091] Tables 2 and 3 show the average values of the crystallinity index α, crystallinity index β, and puncture strength of each sample piece. As shown in Table 2, it was confirmed that a laminate with a large crystallinity index α, β has a higher puncture strength than a laminate with a small crystallinity index α, β. Comparing Tables 2 and 3, no change in the crystallinity index α, β and puncture strength was observed depending on whether or not retort treatment was performed, and it was confirmed that retort treatment does not have much effect on the crystallinity index α, β and puncture strength. From the results of Tables 1, 2, and 3, it was confirmed that a laminate with high puncture strength can be produced by using a nylon 6 film with a high crystallinity index. It was also confirmed that a packaging bag with sufficiently high puncture strength can be produced by using a laminate with a large crystallinity index. [Industrial Applicability]
[0092] According to the present disclosure, it is possible to provide a laminate having a sufficiently high puncture strength in a laminate having a polyethylene terephthalate film, a nylon 6 film, and a sealant layer in this order, as well as a packaging bag and a packaging body including such a laminate. [Explanation of symbols]
[0093] 10...polyethylene terephthalate film, 20...nylon 6 film, 30...sealant layer, 40...printed layer, 100, 100a, 100b, 100c...laminate, S1...first adhesive layer, S2...second adhesive layer, X...surface, 200...packaging body, C...center, 21...content, 22...container, 31...upper end sealed portion, 31a...upper end, 32...sealed portion, 33, 34...side end sealed portion, 35, 36...lower end sealed portion, 41...notch, 50...steam vent portion, 53...non-sealed portion, 300, 301...packaging bag.
Claims
1. A laminate comprising a polyethylene terephthalate film, a nylon 6 film, and a sealant layer in this order, The surface of the laminate on the side of the polyethylene terephthalate film was measured by X-ray diffraction, and the peak intensity value detected when 2θ was 19.5° was defined as I 0 , the peak intensity value of the (002) plane of nylon 6 is I 1 Then, I 1 / I 0 The laminate, wherein the thickness is 11.5 or more.
2. The peak intensity value of the (100) plane of the polyethylene terephthalate when the surface was measured by X-ray diffraction was I 2 Then, I 2 / I 0 The laminate according to claim 1, wherein the elastic modulus is 10.6 or more.
3. 3. The laminate according to claim 1, wherein the nylon 6 film is a stretched film obtained by a tubular process.
4. 3. The laminate according to claim 1 or 2, having a puncture strength of 17 N or more.
5. The surface of the nylon 6 film alone was measured by X-ray diffraction, and the peak intensity value detected when 2θ was 19.5° was defined as I 0 , the peak intensity value of the (002) plane of nylon 6 is I 1 Then, I 1 / I 0 3. The laminate according to claim 1 or 2, comprising the nylon 6 film having a modulus of 25 or more.
6. The surface of the polyethylene terephthalate film alone was measured by X-ray diffraction, and the peak intensity value detected when 2θ was 19.5° was defined as I 0 , the peak intensity value of the (100) plane of polyethylene terephthalate is I 2 Then, I 2 / I 0 The laminate according to claim 1 or 2, comprising the polyethylene terephthalate film having a modulus of 41 or more.
7. 3. The laminate according to claim 1, wherein the nylon 6 film has a puncture strength of 11.5 N or more.
8. The laminate according to claim 1 or 2, wherein the nylon 6 film has a thickness of 10 to 25 μm.
9. The laminate according to claim 1 or 2, wherein the polyethylene terephthalate film has a thickness of 9 to 25 μm.
10. A packaging bag comprising the laminate according to claim 1 or 2.
11. A package comprising the packaging bag according to claim 10 and an item contained in a storage portion of the packaging bag.
Citation Information
Patent Citations
Puncture-resistant five-layer co-extrusion polyester film and preparation method thereof
CN103358634A
Multilayer barrier film for VSP packaging, method of packaging and packages obtained therewith
EP2386411A1
Lid material for aseptic rice-packing container and aseptically packed rice with use of it
JP2002019003A
Rice cake individual packaging material and individual rice cake packaged body using the same
JP2003146383A
Packaging material for retort and retort-packaged product using the same
JP2004106350A